Insights into engineering work for future surveyors - Mirzayev Jonibek Oltiyevich; Abduraxmonov Doniyorbek Ravshan o‘g‘li; Shukurullayev Sayfullo Dilshod o‘g‘li (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article describes the conduct of geodetic work on engineering work by young specialists entering this field, and provides final conclusions and proposals for the work performed.